2012
DOI: 10.1080/10803548.2012.11076920
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects Associated With Long-Term Occupational Exposure of Employees of a Chlor-Alkali Plant to Mercury

Abstract: This study aimed to evaluate possible health effects associated with long-term occupational exposure to low levels of mercury vapors. Forty-six subjects exposed to mercury and 65 healthy unexposed employees were studied. The subjects were administered a questionnaire on experienced symptoms and underwent clinical examinations as well as routine biochemical tests. Atmospheric and urinary concentrations of mercury were measured, too. Environmental concentrations of mercury were estimated to be 3.97 ± 6.28 μg/m(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…22 Nevertheless, the growing concerns about environmental and health hazards of mercury poisoning have severely curtailed its use and further development. 23,24 For example, Ontario Minamata disease in Canada and Japan caused by mercury poisoning has severe negative impacts on human health. Membrane-based electrolysis developed slowly until the invention of the homogeneous cation-selective membrane.…”
Section: Progress Of Chlor-alkali Productionmentioning
confidence: 99%
“…22 Nevertheless, the growing concerns about environmental and health hazards of mercury poisoning have severely curtailed its use and further development. 23,24 For example, Ontario Minamata disease in Canada and Japan caused by mercury poisoning has severe negative impacts on human health. Membrane-based electrolysis developed slowly until the invention of the homogeneous cation-selective membrane.…”
Section: Progress Of Chlor-alkali Productionmentioning
confidence: 99%
“…Exposures to MeHg, which is present at high concentrations in seafood diets, are common and ubiquitous; MeHg has a higher entry rate into the CNS compared with inorganic mercurials, rendering it an important neurotoxicant (Aschner et al, 2007b; Debes et al, 2006). Occupational exposures to Hg (mainly in the form of elemental mercury, Hg°), due to its use in industry (Neghab et al, 2012) and artisanal gold mining (Lubick, 2010), are also of toxicological relevance. In addition, iatrogenic exposures to Hg continue to represent a concern.…”
Section: Mercurymentioning
confidence: 99%
“…Studies have showed that short-term exposure to high doses of MeHg or chronic mercury exposure produces sensory and motor deficits, including impaired color vision and general visual acuity ( Barboni et al, 2009 ; Feitosa-Santana et al, 2010 ; Heath et al, 2010 ; Neghab et al, 2012 ). Thus, MeHg exposure in the present study might impair learning process specifically or by impairing sensory or motor processes that are necessary for learning to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Even the 0.1 μM MeHg group of older zebrafish that showed more general and profound behavioral deficits was able to perceive the body shock and the opening under the divider, and was able to swim through the opening under the divider to escape the body shock as indicated by their higher level of escape responses during training. Furthermore, visual deficits produced by MeHg exposure tend to occur following chronic mercury exposure, and include color vision impairments and diminished visual acuity ( Barboni et al, 2009 ; Feitosa-Santana et al, 2010 ; Neghab et al, 2012 ). In the present study, the 2-week MeHg exposure was short-term and a bright light was used as the CS.…”
Section: Discussionmentioning
confidence: 99%